New manifestations and meanings of Orthodox Lity - preservation of identity and sacralization of space and time in the Belgrade’s (and broader Serbian) context - Todorović Ivica (Glasnik Etnografskog Instituta SANU, 2023)
In the text, we primarily deal with the observation of the latest manifestations of the Orthodox lity procession ritual and ways of sacralising the space on the example of Belgrade. Accordingly, attention is also paid to the symbolism of different spatial landmarks, which is emphasized at the level of several semantic layers. Recent events have once again actualized the importance of the Lity procession ritual - deeply rooted in both folk tradition and religion - as well as its manifestations, both in the Republic of Serbia and in the wider Serbian ethnic area. The basic and most visible function of Lity is the consecration and marking of space, but also of time, with special significance for a certain ethnic-social context, community or place. However, Lity also have a pronounced cohesive and identity function, as was particularly clearly demonstrated in the example of the defense of holy sites, i.e. of basic religious rights, precisely through Lity in Montenegro. Consequently, Lity proved to be one of the most effective weapons against attempts to deconstruct the Serbian identity. In accordance with the relevant indicators, in our work, with a multidisciplinary approach, various structural and semantic dimensions and possibilities of Lity are considered. This primarily refers to the level of the Belgrade area, but in a more general sense it is also directly related to field and other research on related issues, which were carried out in a much wider area during the previous decades.